Budgetary Approach to Project Management by Percentage of Completion Method - Leszek Borowiec (Contemporary Economics)
Efficient and effective project management process is made possible by the use of methods and techniques of project management. The aim of this paper is to present the problems of project management by using Percentage of Completion method. The research material was gathered based on the experience in implementing this method by the Johnson Controls International Company. The article attempts to demonstrate the validity of the thesis that the POC project management method, allows for effective implementation and monitoring of the project and thus is an effective tool in the managing of companies which exploit the budgetary approach. The study presents planning process of basic parameters affecting the effectiveness of the project (such as costs, revenue, margin) and characterized how the primary measurements used to evaluate it. The present theme is illustrating by numerous examples for showing the essence of the raised problems and the results are presenting by using descriptive methods, graphical and tabular.